2019
DOI: 10.1128/iai.00789-18
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Central Noradrenergic System by Toxoplasma gondii Infection

Abstract: Toxoplasma gondii is associated with physiological effects in the host. Dysregulation of catecholamines in the central nervous system has previously been observed in chronically infected animals. In the study described here, the noradrenergic system was found to be suppressed with decreased levels of norepinephrine (NE) in brains of infected animals and in infected human and rat neural cells in vitro. The mechanism responsible for the NE suppression was found to be downregulation of dopamine ␤-hydroxylase (DBH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 71 publications
(106 reference statements)
0
13
0
2
Order By: Relevance
“…These combined results suggest that miR-132 may be a common target of a broad range of pathogens and may represent a general response to infection. It is also worth noting that other researchers have reported dysregulation of dopamine pathways during Toxoplasma infection, suggesting possible links to nervous system abnormalities (Syn et al, 2018; Alsaady et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…These combined results suggest that miR-132 may be a common target of a broad range of pathogens and may represent a general response to infection. It is also worth noting that other researchers have reported dysregulation of dopamine pathways during Toxoplasma infection, suggesting possible links to nervous system abnormalities (Syn et al, 2018; Alsaady et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, the fact that anomalous accumulation of dopamine between synapses could cause various pathological processes such as increased dopamine concentration, synaptic structure disorder, proliferation of neural progenitor cells, and migration of neuron cells (Ortiz-Guerrero et al, 2020), thus may lead to the occurrence of psychiatric behavioral disorders. Alsaady et al (2019) also found that T. gondii could regulate the expression of dopamine b-hydroxylase (DBH) gene, which is responsible for dopamine synthesis of NE, resulting in a decrease in NE concentration in human/rat neurons that were cultured in vitro and were infected with tachyzoites, but the decrease in NE in rat brain tissue was limited in males. The authors also demonstrated that this sexspecific downregulation of DBH was associated with host behavioral changes.…”
Section: Dopamine-norepinephrine Hypothesismentioning
confidence: 99%
“…Additionally, the expression of dopamine β-hydroxylase (DBH), an enzyme that converts DA to NE, was specifically downregulated in the infected cells and male mice brain tissues. It leads to the suppression of NE and alternation of sociability and arousal ( Alsaady et al., 2019 ). In particularly, reduction in DBH may be a specific neuron response to T. gondii infection, since human cytomegalovirus could not induce similar downregulation of DBH.…”
Section: Advances Of Epigenetic Regulation In T Gondii ...mentioning
confidence: 99%
“…It has been proposed that an interplay between neuroinflammation and neurotransmission may underlie cognitive changes associated with chronic toxoplasmosis (160). Indeed, reported neurotransmission alterations during toxoplasmosis in rodents include dysregulations of catecholamines, GABA and glutamate (161)(162)(163).…”
Section: Control Of Infection By Brain Parenchymal Cellsmentioning
confidence: 99%